1990
DOI: 10.1029/gl017i006p00897
|View full text |Cite
|
Sign up to set email alerts
|

Upstream waves at Mars: Phobos observations

Abstract: The region upstream from the Mars subsolar bow shock is surveyed for the presence of MHD wave phenomena using the high temporal resolution data from the MAGMA magnetometer. Strong turbulence is observed when the magnetic field is connected to the Mars bow shock in such a way as to allow diffuse ions to reach the spacecraft. On 2 occasions this turbulence occurred upon crossing the Phobos orbit. Also weak, ∼0.15 nT, waves are observed at the proton gyro frequency. These waves are left‐hand elliptically polarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 142 publications
(89 citation statements)
references
References 12 publications
4
85
0
Order By: Relevance
“…High-frequency emissions, broadband electric noise, whistler modes and ULF fluctuations were typically recorded by the wave instrument before the Phobos-2 spacecraft crossed the bow shock. The enhanced level of magnetic field oscillations in the ULF range upstream the Martian bow shock was reported by Russell et al (1990) and Delva and Dubinin (1998). Simultaneous plasma observations have revealed the presence of both ions and electrons reflected from the bow shock and streaming back to the solar wind (Kiraly et al, 1991;Barabash and Lundin, 1991).…”
Section: Introductionmentioning
confidence: 79%
“…High-frequency emissions, broadband electric noise, whistler modes and ULF fluctuations were typically recorded by the wave instrument before the Phobos-2 spacecraft crossed the bow shock. The enhanced level of magnetic field oscillations in the ULF range upstream the Martian bow shock was reported by Russell et al (1990) and Delva and Dubinin (1998). Simultaneous plasma observations have revealed the presence of both ions and electrons reflected from the bow shock and streaming back to the solar wind (Kiraly et al, 1991;Barabash and Lundin, 1991).…”
Section: Introductionmentioning
confidence: 79%
“…It may be possible to detect these waves using the ARTEMIS vector magnetic field data. Waves from pickup ions have been identified in the plasma environments of many solar system bodies, including Venus, Mars, and even the moons of the giant planets (Russell et al 1990;Kivelson et al 1996;Paterson et al 1999;Grebowsky et al 2004;Dougherty et al 2006;Russell and Blanco-Cano 2007;Delva et al 2008), and their presence or absence can be used to constrain the local density of pickup ions, and therefore the source strength.…”
Section: Exospheric Ions and Plasma Pick-upmentioning
confidence: 99%
“…The proton gyrofrequency in a background field of B=4 nT is f P =eB/(2π m p )=61 mHz. These waves at the local proton gyrofrequency (PCWs) are low amplitude waves (≈0.15 nT), and they have been described by Russell et al (1990) using ASPERA data measured on Phobos-2 and by Brain et al (2002) using MGS magnetic field data. As Brain et al (2002) stated, these waves were not observed at larger subsolar distances than 3 R M from Mars.…”
Section: Romap Datamentioning
confidence: 99%
“…The first signature of the upstream waves in ROMAP data was obtained at 01:36 UT, when Rosetta was at a distance of about 2 R M from the surface of the planet. Russell et al (1990) concluded that these left-hand polarized waves were formed by ionization of the Martian hydrogen exosphere upstream of the shock. Barabash et al (1991) confirmed this conclusion by results from ASPERA, which observed ring distributions of pickup protons from the hydrogen corona.…”
Section: Romap Datamentioning
confidence: 99%